2013
DOI: 10.4103/0250-474x.117426
|View full text |Cite
|
Sign up to set email alerts
|

Stability-indicating HPLC method for simultaneous determination of montelukast and fexofenadine hydrochloride

Abstract: A simple, specific, accurate, and stability-indicating reversed-phase high-performance liquid chromatographic method was developed for the simultaneous determination of montelukast and fexofenadine hydrochloride, using a Lichrospher® 100, RP-18e column and a mobile phase composed of methanol:0.1% o-phosphoric acid (90:10 v/v), pH 6.8. The retention times of montelukast and fexofenadine hydrochloride were found to be 10.16 and 12.03 min, respectively. Linearity was established for montelukast and fexofenadine h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Various ultraviolet (UV) and high-performance liquid chromatographic (HPLC) assay methods are also reported in literature for the estimation of phenylephrine and fexofenadine individually and in combination with other drugs [7][8][9][10][11][12]. According to literature survey, there is no official method for the simultaneous estimation of phenylephrine and fexofenadine by reverse phase-HPLC (RP-HPLC) in combined tablet dosage forms.…”
Section: Fexofenadine Is Chemically Named As 2-(4-{1-hydroxy-4-[4(hydmentioning
confidence: 99%
“…Various ultraviolet (UV) and high-performance liquid chromatographic (HPLC) assay methods are also reported in literature for the estimation of phenylephrine and fexofenadine individually and in combination with other drugs [7][8][9][10][11][12]. According to literature survey, there is no official method for the simultaneous estimation of phenylephrine and fexofenadine by reverse phase-HPLC (RP-HPLC) in combined tablet dosage forms.…”
Section: Fexofenadine Is Chemically Named As 2-(4-{1-hydroxy-4-[4(hydmentioning
confidence: 99%
“…These methods include high performance liquid chromatography (HPLC) (Uno et al, 2004;Pankaniya et al, 2013;Krakus et al, 2008), capillary electrophoresis (Breier et al, 2005;Mikus et al, 2005), mass spectrometric methods (Guo et al, 2010;Hofmann et al, 2002), spectrophotometric methods (Gazy et al, 2002;Naravana and Veena, 2010;Ashour et al, 2013), and chemiluminescence (CL) method (Al-Lawati et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature found a few methodologies for simultaneous measurements of MON and FEX. These methods included a chemometric method [27] and chromatographic methods [28][29][30].…”
Section: Introductionmentioning
confidence: 99%